2009
DOI: 10.1111/j.1745-6622.2009.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Private Equity vs. PLC Boards in the U.K.: A Comparison of Practices and Effectiveness

Abstract: The consistently higher returns generated by the most successful private equity firms have been attributed in part to their willingness to take on high levels of debt and their ability to exit from their investments at attractive multiples. But recent research suggests that the largest contributor to the superior performance of the best PE firms has been their ability to improve the operating performance of the companies they buy. And as the authors of this article argue, a key source of such improvements are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…2007). This is longer than the average investment in listed company stocks by institutional investors (Acharya, Kehoe, and Reyner 2009; Gottschalg 2007). Studies have found little evidence of short‐termism as a result of private equity ownership when measuring R&D, investment, and sustainability (Cumming, Siegel, and Wright 2007; Watt and Galgoczi 2009:203).…”
Section: Time To Exit Anglo‐saxon Investors and Foreign Investorsmentioning
confidence: 94%
“…2007). This is longer than the average investment in listed company stocks by institutional investors (Acharya, Kehoe, and Reyner 2009; Gottschalg 2007). Studies have found little evidence of short‐termism as a result of private equity ownership when measuring R&D, investment, and sustainability (Cumming, Siegel, and Wright 2007; Watt and Galgoczi 2009:203).…”
Section: Time To Exit Anglo‐saxon Investors and Foreign Investorsmentioning
confidence: 94%
“…(2007), and Kaplan and Stromberg (2009) for comprehensive literature surveys). Evidence also points to governance advantages of PE firms’ boards compared to publicly listed companies (Acharya et al ., 2009).…”
Section: Private Equity Exit and Buy‐out Performancementioning
confidence: 99%
“…Empirically, for a portfolio firm, diffusion of the PEBM template varies from formal adoption to vicarious learning and centres on the ability of investor‐owner‐managers to achieve ceremonial if not institutional alignment between investor‐owner interests, those of managers and workers in portfolio firms. As recent studies demonstrate downsizing, asset sales and financial engineering represent three areas of activity in which private equity investors exercise efficiencies in management practice over listed or other private firms (see Acharya et al ., 2009; Achleitner et al ., 2009; Bacon et al ., 2010). In the cases under consideration, asset sales were coercively diffused in all portfolio firms to represent a clear‐cut example of decisive restructuring by powerful outsiders.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, any debts incurred within portfolio firm restructuring and refinancing remain with the firm, not its current owners. While these strategies appear to represent a coherent ‘best practice’ to portfolio firm restructuring, firms that are not governed by the PEBM have successfully ‘mimicked’ strategies associated with the model to raise efficiency levels (Acharya et al ., 2009; Achleitner et al ., 2009). This suggests that diffusion of this ‘best practice’ in restructuring and financial engineering may be adopted by firms listed or otherwise which are not governed by the PEBM.…”
Section: Discussionmentioning
confidence: 99%